Guo jia shi zen yang lian cheng de = The history of the countries II - Sai, Lei (Beijing : Zhong guo zhi gong chu ban she, 2019)
This book introduces Russia, a fighting nation that has developed from a border island country to a world economic power, with a mixture of Japanese and Mongolian genes and European descent, Thailand, which was protected from aggression in World War II, and the dream of returning to ancient Greece. India, which is deeply troubled by the (3z(Bcaste system,(3y (BVietnam, which is not afraid of powerful enemies and dares to challenge the United States, Singapore, which cannot develop without the whip, and Iran, which developed from the Persian empire spanning Asia, Europe and Africas
Text in Chinese script.
Keywords: World history; World history -- Comic books, strips, etc